In vitro and in vivo characterization of poly(glycerol sebacate urethane) scaffolds for tendon tissue engineering - Xenou, Zacharoula (My University, 2023)
One of the promising fields in Biomedical Engineering today is tissue engineering. This is specifically important in the application of tendon regeneration. Tendons are characterized by a slow and painful, recovery and usually partial and ineffective healing. More specifically, tendon engineering is a promising field that aims to enhance tendon healing or regeneration. Tendon tissue engineering is an interdisciplinary field that combines biology, chemistry, and engineering to support tendon development. The common general strategy used to achieve this goal is the creation of a scaffold in combination with biological factors and the appropriate structure for tendon regeneration. Thus, the aim of this study was to fabricate a synthetic scaffold from poly(glycerol sebacate urethane) that mimics the structure and properties of the tendon to be replaced. In the present study, poly(glycerol sebacate urethane glycerol) scaffolds with anisotropic porous microstructure were fabricated using the freeze-drying method. Scaffolds with different amounts of reactants were synthesized and tested for their suitability for tendon tissue engineering. More specifically, the microstructure of the scaffolds was studied in terms of pores and their anisotropy. In addition, an optimal strategy of cell implantation was investigated along with the in vitro biocompatibility of the scaffolds. Subsequently, the scaffolds were implanted subcutaneously in mice to examine their in vivo biocompatibility, their biodegradation rate and tissue growth through the scaffold. Finally, since the aim was to apply it to tendon tissue engineering, the most suitable scaffold was implanted in situ in mouse tendon-model to study and investigate the distribution of the tissue created and its similarity with the native tendon tissue. By the end of this study anisotropic porous PGSU scaffolds were fabricated which were found to be biocompatible in vitro and in vivo. The implantation of the scaffold fabricated in the flexor tendon in mouse model showed to enhance tissue ingrowth and the tissue regenerated was anisotropically structured mimicking the microstructure of the tendon.
Keywords: tendon tissue engineering; porous anisotropic scaffolds; in vitro biocompatibility; biodegradation rate; in vivo tissue ingrowth